Hierarchical Virtual Screening Based on Rocaglamide Derivatives to Discover New Potential Anti-Skin Cancer Agents - dos Santos, Igor V.F.; Borges, Rosivaldo S.; Silva, Guilherme M.; de Lima, Lúcio R.; Bastos, Ruan S.; Ramos, Ryan S.; Silva, Luciane B.; da Silva, Carlos H. T. P.; dos Santos, Cleydson B. R. (Frontiers in Molecular Biosciences, 2022)
Skin Cancer (SC) is a common disease among caucasians and several anticancer drugs have been discovered through screening for natural plant-derived products and molecular modeling. The phytochemical Rocaglamide A (Roc-A) and its derivatives rises as an interesting set of reference compounds due to their in vitro cytotoxic activity with SC cell lines. In view of this, we performed a hierarchical virtual screening study considering Roc-A and its derivatives, with the aim to find new chemical entities with potential activity against SC. For this, we selected 15 molecules (Roc-A as the pivot molecule and 14 derivatives) and initially used them in docking studies to elucidate and validate their interactions with Chk1 (Checkpoint Kinase 1) as a target for SC. This allowed us to compile and use them as a training set to build a robust pharmacophoric model, validated by Pearson's correlation values (p) and hierarchical cluster analysis (HCA), subsequentially submitted to prospective virtual screening using the Molport® database. Outputted compounds were then selected considering their similarities to pivot molecule, followed by analysis of predicted of toxicity and pharmacokinetic properties and, finally, consensus molecular docking analysis using three software. 10 promising compounds were selected and analyzed in terms of their properties and structural features and, also, considering their previous reports in literature. In this way, the 10 promising virtual hits found in this work point to their potential as anti-SC agents, and further investigations concerning their biological tests shall be conducted.